2017
DOI: 10.1016/j.ygyno.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with topotecan, paclitaxel, and bevacizumab improves progression-free survival in recurrent small cell neuroendocrine carcinoma of the cervix

Abstract: Objectives To assess if the combination of topotecan, paclitaxel, and bevacizumab (TPB) was active in recurrent SCCC and to compare the survival of patients with SCCC who received TPB to a group of women with SCCC who did not receive this regimen. Methods We retrospectively analyzed women with recurrent SCCC who received chemotherapy as primary therapy. Women treated with TPB for first recurrence were compared to women treated with non-TPB chemotherapy. Results Thirteen patients received TPB, and 21 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…The largest series of women analyzing the treatment efficacy of chemotherapy among women with recurrent NECC was published by Frumovitz et al [ 140 ]. They compared 13 patients who received the combination of topotecan, paclitaxel, and bevacizumab (TPB) with 21 patients receiving other regimens, mostly a platinum-based regimen with or without a taxane.…”
Section: Resultsmentioning
confidence: 99%
“…The largest series of women analyzing the treatment efficacy of chemotherapy among women with recurrent NECC was published by Frumovitz et al [ 140 ]. They compared 13 patients who received the combination of topotecan, paclitaxel, and bevacizumab (TPB) with 21 patients receiving other regimens, mostly a platinum-based regimen with or without a taxane.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al[ 33 ] found that patients who underwent NACT plus radical surgery had a lower rate of distant recurrence compared with those who underwent radical surgery alone (P = 0.029), and deduced that although platinum-based NACT cannot improve the survival rate of SCCC, it can control distant recurrence[ 34 ]. In a retrospective analysis of 13 patients with SCCC receiving a TPB regimen (topotecan, paclitaxel, and bevacizumab) and 21 patients who did not receive TPB conducted by Frumovitz et al[ 35 ], it was found that the median progression-free survival was 7.8 months in the TPB group and 4.0 months in the non-TPB group (P = 0.001), suggesting that a TPB regimen improves survival. Although very few studies on NACT were included in this study, the results show that NACT is closely associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our regimen of choice for patients with recurrent or progressive disease who have already been treated with a platinum and etoposide combination is a triplet regimen including topotecan, paclitaxel, and bevacizumab given in the same manner as in Gynecologic Oncology Group (GOG) 240, a phase III study in patients with recurrent cervical cancer (squamous cell carcinoma, adenocarcinoma, and adenosquamous carcinoma) 58. The rationale for this schema is that first this regimen is tolerable in women who have previously undergone definitive chemoradiation.…”
Section: Recurrent Diseasementioning
confidence: 99%